Penerapan Internet of Things (IoT) Untuk Monitoring Kondisi Tanah Gembur Pada Tanaman Hias Pucuk Merah Secara Real-Time - Anggit Wahyu Edwinata; Kusnandar Kusnandar; Presa Taruna Oliver (Journal of Informatics Management and Information Technology, 2026)
This research aims to develop a real-time Internet of Things (IoT) based loose soil pH monitoring system for application to red shoots ornamental plants. The system designed in this research combines a soil pH sensor to measure soil acidity levels, a NodeMCU ESP32 microcontroller as a data processor, a 16x2 I2C LCD to display local information, and provides real-time data to users through the Blynk application. The purpose of developing this system is that users can easily monitor soil conditions in real-time and take necessary actions to increase plant productivity, especially red shoots ornamental plants that require special attention to their soil conditions. This research is expected to be a continuation of previous research which is still in the design stage of a soil pH monitoring system. This development is focused on a different research object, namely loose soil pH in red shoots ornamental plants, so it is expected to be able to produce a more practical, applicable loose soil pH monitoring system, and provide a real contribution to the management of red shoots ornamental plants effectively and efficiently.